2011
DOI: 10.1152/ajpendo.00077.2011
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut sweet taste receptor in regulating GLP-1, PYY, and CCK release in humans

Abstract: Gerspach AC, Steinert RE, Schönenberger L, Graber-Maier A, Beglinger C. The role of the gut sweet taste receptor in regulating GLP-1, PYY, and CCK release in humans. Am J Physiol Endocrinol Metab 301: E317-E325, 2011. First published May 3, 2011 doi:10.1152/ajpendo.00077.2011The recent identification of sweet taste receptors in the gastrointestinal tract has important implications in the control of food intake and glucose homeostasis. Lactisole can inhibit the sweet taste receptor T1R2/T1R3. The objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 46 publications
6
136
1
Order By: Relevance
“…Various studies have tried to elucidate the physiological role of gut taste receptors in humans. Gerspach et al 37 demonstrated that lactisole, a T1R1/T1R3 (sweet) antagonist, induced a significant reduction in GLP-1 and PYY but not CCK secretion, in response to intragastric and intraduodenal glucose administration. Our study demonstrates, for the first time, that bitter taste receptors are also involved in the physiological mechanisms that control appetite in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have tried to elucidate the physiological role of gut taste receptors in humans. Gerspach et al 37 demonstrated that lactisole, a T1R1/T1R3 (sweet) antagonist, induced a significant reduction in GLP-1 and PYY but not CCK secretion, in response to intragastric and intraduodenal glucose administration. Our study demonstrates, for the first time, that bitter taste receptors are also involved in the physiological mechanisms that control appetite in humans.…”
Section: Discussionmentioning
confidence: 99%
“…These include GPR119 (40), which is activated by N-acylethanolamines (41), GPR120 (42) and GPR40 (43), which are activated by long-chain fatty acids (LCFAs), GPR41 (44), GPR43 (45) and FFAR2 (46), which are activated by short-chain fatty acids (SCFA), and TGR5 (8), which is activated by bile acids. In addition, taste receptors (primarily T1R2/T1R3 and a-gustducin) in the stomach and intestine seem to regulate the secretion of GLP1 (47,48,49). Paracrine, neuronal and neurohormonal mechanisms may also be important for the facilitation of postprandial GLP1 secretion (50,51,52,53).…”
Section: Glp1 Secretionmentioning
confidence: 99%
“…T1R2-T1R3 agonists enhance intestinal glucose absorption ), incretin response (Brown et al 2009), insulin secretion (Pepino et al 2013), and adipocyte differentiation (Masubuchi et al 2013). Sodium lactisole, a T1R2-T1R3 inhibitor, has been shown to lower insulin secretion and GLP-1 secretion in vitro (Jang et al 2007;Nakagawa 2011) and in vivo (Gerspach et al 2011). Given that clofibric acid inhibits T1R2-T1R3, it is possible that its metabolic effects may be due, in part, to T1R inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic knock-out studies represent the ultimate loss of function of the T1R2-T1R3 receptors, but pharmacological inhibition may have similar, albeit less potent, effects on metabolism. It has been shown that the T1R3 inhibitor sodium lactisole increases plasma glucose 'area under the curve' (AUC) response to a glucose load (Gerspach et al 2011). This effect is consistent with reduced stimulation of insulin by T1Rs (Jiang et al 2005;Hamano et al 2015).…”
Section: Introductionmentioning
confidence: 99%